Accessing finance among women-owned small businesses: Evidence from lower Manya Krobo municipality, Ghana - Simon Boateng; Kwabena Osei Poku (Journal of Global Entrepreneurship Research, 2019)
The study examined the constraints to accessing finance among women-owned small businesses in the Lower Manya Krobo Municipality in the Eastern Region, Ghana. We employed largely qualitative methods using the case study approach. The purposive and simple random sampling techniques were used to select 50 respondents. In-depth interview guide and focused group discussion were used to gather data from participants. The data were thematically analysed. The study revealed that there are constraints of poor market demand and lack of capital and credit. In furtherance, although collaterals exist for small businesses, they are being discriminated against women micro-entrepreneurs due to the patrilineal inheritance system of the area. Again, it was found that the financial institutions generally considered giving loans as risky as a result of lack of codified business strategy and plan, proper costing of business and informational asymmetries about business owners and their businesses. The study, therefore, recommends that the activities of women micro businesses in the private sector of the economy should be urgently recognised within the lending models and structures as they constitute a valuable area of economic growth. The National Board for Small Scale Industries (NBSSI) through the Business Advisory Centre (BAC) should organise educational and training seminars regularly to educate women micro-entrepreneurs on business management to be able to negotiate effectively on the various landed properties in such a patriarchal system to reduce high start-up mortality of women micro businesses. The study further recommends to the National Identification Authority to take cogent action to fast-track the identification system of citizens as it remains one of the major factors to reduce loan risks and interest rates.
Keywords: 650; Constraints to accessing finance; women-owned small businesses; Start-up mortality; patrilineal inheritance; patriarchal system